A study of deaths due to railway fatalities at a tertiary care hospital mortury 2015-16 - Kumar, P. Ravi (International Journal of Research in Medical Sciences, 2017)
Background: Railway accidents according to the NCRB, 25,006 people died and 3,882 were injured in a total of 28,360 railway accidents across the country in last year. Railway crossing accidents like India has an extensive rail network with high levels of injury and violence. Methods: This study was conducted at Forensic medicine department, PIMS (pondicherry institute of medical sciences). The study group consisted of all the victims reporting to PIMS hospital Mortuary, during the period of study (January 2015-January 2016) were subjected to thorough post mortem examination and the pattern of injuries were noted. Results: A total of 300 postmortems, performed at the mortuary of the Dept. of Forensic Medicine, DMC during the period of January to December 2016, were studied. Of them 164 (54.89%) cases were of accidents, 72 (23.19%) cases were suicide, 54 (17.12%) cases homicide, 8 (2.46%) cases undetermined and 2 (0.80%) cases were of natural deaths. In this study accidental deaths were commonest, seen in (72.12%) cases followed by suicidal (20.63%) and least was homicidal seen in (7.16%) cases. Conclusions: Deaths have occurred in association with railway since the inception of railway in the present study males are commonest victims of railway deaths which concurs with studies conducted by other authors. Helpline numbers should be printed inside the coaches to inform the authorities in case of emergency. Railway should strictly implement the laws of railway acts and the people should be penalized for breaking the rules for the safety of passengers.